Facile Green Synthesis of Silver Nanoparticles Using Rubus rosifolius Linn Aqueous Fruit Extracts and Its Characterization - Martin, Marilen M.; Sumayao Jr., Rodolfo E. (Applied Science and Engineering Progress, 2022)
Rubus rosifolius Linn is a wild raspberry found in the Philippines. The fruit extract is found to be rich in flavonoids, terpenoids, tannins, and polyphenols. It has been shown to contain interesting profiles of antioxidants and it is not previously explored as a reducing agent, specifically in the field of bio-nano research. Some of these antioxidants have been documented to have anti-cancer potential. In this study, the fruit extracts of sampinit were used as a reducing agent for the synthesis of silver nanoparticles (AgNPs) via a ‘one-pot’ facile approach. Sampinit aqueous fruit extract-AgNPs (SAFE-AgNPs) were synthesized by reducing silver ions using sampinit extract. Optical, chemical, and morphological properties of the synthesized SAFE-AgNPs were characterized. Maximal absorption of SAFE-AgNPs was observed at 415 nm which is associated with the characteristic surface plasmon resonance profile of AgNPs. SAFE-AgNPs displayed highly stable and homogeneous nanoparticles with hydrodynamic size of 85.6 ± 0.98 nm and a zeta potential of –29.5 ± 0.96 mV. HR-TEM analysis of a single crystalline image of SAFE-AgNPs corresponds to hexagonal diffraction pattern and the AgNPs were coated with soft carbon-rich materials. EDX and XRF analysis showed that SAFE-AgNPs are chiefly composed of silver (Ag) and carbon (C), where C was largely localized on the surface of AgNPs. FTIR analysis showed that SAFE-AgNPs contains key chemical functional groups associated with sampinit-derived phytoconstituents. Overall, the biosynthesized SAFE-AgNPs produced small size, spherical shape, and monodisperse population which can be a candidate therapeutic agent for the treatment of various diseases such as cancer.